Upregulation of the APE1 and H2AX genes and miRNAs involved in DNA damage response and repair in gastric cancer - Manoel-Caetano, Fernanda S. [UNESP]; Rossi, Ana Flávia T. [UNESP]; Calvet de Morais, Gabriela [UNESP]; Severino, Fábio Eduardo [UNESP]; Silva, Ana Elizabete [UNESP] (Elsevier, 2019)
Gastric cancer remains one of the leading causes of cancer-related death worldwide, and most of the cases are associated with Helicobacter pylori infection. This bacterium promotes the production of reactive oxygen species (ROS), which cause DNA damage in gastric epithelial cells. In this study, we evaluated the expression of important genes involved in the recognition of DNA damage (ATM, ATR, and H2AX)and ROS-induced damage repair (APE1)and the expression of some miRNAs (miR-15a, miR-21, miR-24, miR-421 and miR-605)that target genes involved in the DNA damage response (DDR)in 31 fresh tissues of gastric cancer. Cytoscape v3.1.1 was used to construct the postulated miRNA:mRNA interaction network. Analysis performed by real-time quantitative PCR exhibited significantly increased levels of the APE1 (RQ = 2.55, p < 0.0001)and H2AX (RQ = 2.88, p = 0.0002)genes beyond the miR-421 and miR-605 in the gastric cancer samples. In addition, significantly elevated levels of miR-21, miR-24 and miR-421 were observed in diffuse-type gastric cancer. Correlation analysis reinforced some of the gene:gene (ATM/ATR/H2AX)and miRNA:mRNA relationships obtained also with the interaction network. Thus, our findings show that tumor cells from gastric cancer presents deregulation of genes and miRNAs that participate in the recognition and repair of DNA damage, which could confer an advantage to cell survival and proliferation in the tumor microenvironment.
Keywords: DNA damage response; DNA repair; Gastric cancer; Gene expression; microRNA